Virologic effects of broadly neutralizing antibody VRC01 administration during chronic HIV-1 infection - Lynch, Rebecca M; Boritz, Eli; Coates, Emily E; DeZure, Adam; Madden, Patrick; Costner, Pamela; Enama, Mary E; Plummer, Sarah; Holman, Lasonji; Hendel, Cynthia S; Gordon, Ingelise; Casazza, Joseph; et al. (Science translational medicine, 2015)
Passive immunization with HIV-1-neutralizing monoclonal antibodies (mAbs) is being considered for prevention and treatment of HIV-1 infection. As therapeutic agents, mAbs could be used to suppress active virus replication, maintain suppression induced by antiretroviral therapy (ART), and/or decrease the size of the persistent virus reservoir. We assessed the impact of VRC01, a potent human mAb targeting the HIV-1 CD4 binding site, on ART-treated and untreated HIV-1-infected subjects. Among six ART-treated individuals with undetectable plasma viremia, two infusions of VRC01 did not reduce the peripheral blood cell-associated virus reservoir measured 4 weeks after the second infusion. In contrast, six of eight ART-untreated, viremic subjects infused with a single dose of VRC01 experienced a 1.1 to 1.8 log10 reduction in plasma viremia. The two subjects with minimal responses to VRC01 were found to have predominantly VRC01-resistant virus before treatment. Notably, two subjects with plasma virus load <1000 copies/ml demonstrated virus suppression to undetectable levels for over 20 days until VRC01 levels declined. Among the remaining four subjects with baseline virus loads between 3000 and 30,000 copies, viremia was only partially suppressed by mAb infusion, and we observed strong selection pressure for the outgrowth of less neutralization-sensitive viruses. In summary, a single infusion of mAb VRC01 significantly decreased plasma viremia and preferentially suppressed neutralization-sensitive virus strains. These data demonstrate the virological effect of this neutralizing antibody and highlight the need for combination strategies to maintain virus suppression.